(untitled) (Journal of Geography and Environmental Management, 2018)
Principles of formation and functioning of natural systems and features of landscape structure of the territory of North Kazakhstan region are among the least studied areas in physical-and-geographical researches of the region. This can be explained by the fact that at the regional level there were no complex landscape-geographical works held within recent years. The article shows the results of the landscape structure study of the North Kazakhstan region territory within the steppe natural zone. Basing on the summary of the collected stock and published literary and cartographic materials, space images and field survey results we studied the peculiarities of geosystems formation, structure and territorial distribution. This work was performed through a complex of approaches including field, landscape-geographical, comparative-geographical and cartographic methods, system and cross analysis, extrapolation, GIS etc. With the help of GIS we conducted mapping of natural complexes of the study area and developed an electronic landscape map. The analysis of the created landscape map allowed us to identify the principles of territorial distribution and relationships of natural complexes of different taxonomic rank. The results of the study can serve as a basis for preparation of various derivative electronic maps on a single landscape basis and can be used for further studies of natural complexes of the region. Understanding the characteristics of formation, functioning and structural organization of geosystems has important practical value.